Factors influencing plasticity in the arrival‐breeding interval in a migratory species reacting to climate change. Issue 21 (16th October 2019) - Low, Matthew; Arlt, Debora; Knape, Jonas; Pärt, Tomas; Öberg, Meit
Abstract: Climate change is profoundly affecting the phenology of many species. In migratory birds, there is evidence for advances in their arrival time at the breeding ground and their timing of breeding, yet empirical studies examining the interdependence between arrival and breeding time are lacking. Hence, evidence is scarce regarding how breeding time may be adjusted via the arrival‐breeding interval to help local populations adapt to local conditions or climate change. We used long‐term data from an intensively monitored population of the northern wheatear ( Oenanthe oenanthe ) to examine the factors related to the length of 734 separate arrival‐to‐breeding events from 549 individual females. From 1993 to 2017, the mean arrival and egg‐laying dates advanced by approximately the same amount ( 5–6 days), with considerable between‐individual variation in the arrival‐breeding interval. The arrival‐breeding interval was shorter for: (a) individuals that arrived later in the season compared to early‐arriving birds, (b) for experienced females compared to first‐year breeders, (c) as spring progressed, and (d) in later years compared to earlier ones. The influence of these factors was much larger for birds arriving earlier in the season compared to later arriving birds, with most effects on variation in the arrival‐breeding interval being absent in late‐arriving birds. Thus, in this population it appears that the timing of breeding is not constrained by arrival for early‐ to midarriving birds, but instead is dependent on local conditions after arrival. For late‐arriving birds, however, the timing of breeding appears to be influenced by arrival constraints. Hence, impacts of climate change on arrival dates and local conditions are expected to vary for different parts of the population, with potential negative impacts associated with these factors likely to differ for early‐ versus late‐arriving birds. Abstract : We examine the interrelationship between the timing of arrival and breeding in a migratory bird. The arrival‐breeding interval was related to the timing of arrival, the age of the bird, and the degree of spring progression and year. The timing of breeding appears to not be constrained by arrival date, but rather dependent on various local conditions.